2022
DOI: 10.1139/cjfas-2021-0089
|View full text |Cite
|
Sign up to set email alerts
|

Simulated pre-spawning catch and release of wild Atlantic salmon (Salmo salar) results in faster fungal spread and opposing effects on female and male proxies of fecundity

Abstract: Atlantic salmon are increasingly being released after capture by anglers. Yet, there are still unknown effects on the fish being subjected to the process of catch and release. Capture too close to spawning could have adverse effects on fish, and such data are important for setting appropriate closed seasons. This study examines how stressors related to catch and release experienced shortly before spawning affects adult mortality, vulnerability to Saprolegnia spp., and reproductive traits. Adult salmon were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Additionally, Atlantic salmon collected near the end of their spawning migration and exposed to disturbed treatments of simulated catch and release (exercise and 120s air exposure) had higher infestation rates of the fungus Saprolegnia spp. over their body, and males had an increase in the maximum duration of sperm motility, whereas females spawned at the usual time but with fewer eggs (Papatheodoulou et al, 2021). However, in a laboratory study, which also used simulated catch and release, egg survival did not differ between salmon that were angled and non‐angled (Booth et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Atlantic salmon collected near the end of their spawning migration and exposed to disturbed treatments of simulated catch and release (exercise and 120s air exposure) had higher infestation rates of the fungus Saprolegnia spp. over their body, and males had an increase in the maximum duration of sperm motility, whereas females spawned at the usual time but with fewer eggs (Papatheodoulou et al, 2021). However, in a laboratory study, which also used simulated catch and release, egg survival did not differ between salmon that were angled and non‐angled (Booth et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, experimental C&R studies have shown that heart rate and stress hormone levels can remain elevated for a significant amount of time after the fish has been released ( Pankhurst and Dedualj, 1994 ; Anderson et al, 1998 ). This in turn can cause immunosuppression, thus making fish more vulnerable to pathogens, such as the opportunistic fungi Saprolegnia spp ( Papatheodoulou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Any stress initiated in these parental fish may then persist into subsequent generations (either directly or indirectly) via parental effects ( Mileva et al, 2011 ; Burton and Metcalfe, 2014 ; Redfern et al, 2017 ), meaning that the offspring of C&R angled fish may in turn share the burden of the stress experienced by their parents. For example, experimental studies on Atlantic salmon have shown that C&R exposure can negatively impact a number of life history traits, such as a female’s total clutch size ( Richard et al, 2013 ; Papatheodoulou et al, 2022 ). Bouchard et al (2022) also found that Atlantic salmon that had undergone C&R angling had lower reproductive success (measured as the number of offspring surviving to 3 months) than non-caught salmon, but the study was unable to tell whether this was due to poorer parental survival, lower breeding success or lower offspring fitness and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in telemetry and biologging techniques have made it increasingly feasible to monitor wild fish and evaluate behavioral responses to angling that are sensitive indicators of physiological stress (Beitinger 1990;Archard et al 2012;Brownscombe et al 2017aBrownscombe et al , 2017bWhitney et al 2018;Sharma 2019). Postrelease behaviors observed in wild-caught fish have included delayed feeding (Meka and Margraf 2007;Sneddon et al 2016) and migration (Lennox et al 2016a(Lennox et al , 2016bBass et al 2018), inhibited reproduction (Schreck et al 2001;Schreck 2010;Papatheodoulou et al 2022), altered habitat use (Hoolihan et al 2011;Brownscombe et al 2014;Raby et al 2018), and reduced swimming performance and/or predator avoidance (Brownscombe et al 2013;Struthers et al 2018;McLean et al 2020). Addressing physiological and behavioral metrics together can provide valuable insight into the relationship between biochemical and organismal stress responses as well as the potential impacts on population-level processes (Fefferman and Romero 2013;Cooke et al 2016;Louison et al 2017;Balasch and Tort 2019).…”
mentioning
confidence: 99%
“…2001; Schreck 2010; Papatheodoulou et al. 2022), altered habitat use (Hoolihan et al. 2011; Brownscombe et al.…”
mentioning
confidence: 99%